Answer:
The first answer and the second answer.
<h3>
Answer: -6, 7, -8</h3>
Start with the sequence {1, 2, 3, 4, 5, 6, 7, 8, ...}
Then change the sign of every other term so you'll have the first term positive, the second term negative, and so on.
That updates to {1, -2, 3, -4, 5, -6, 7, -8, ...}
Every odd term (1,3,5,..) is positive while every even term (-2,-4,-6) is negative.
Do you need it explained or just the answer
substitute for your equation;
h(x) = f(x) - g(x)
h(x) = (3x + 2) - (-2x -4)
h(x) = 3x + 2 + 2x + 4 (minus and minus = addition)
h(x) = 3x + 2x + 2 + 4 (combine like terms)
h(x) = 5x + 6
Hope that helps! :D
Answer:
4
Step-by-step explanation:
4 is the answer